Tutoring and mentoring programs in Brazilian universities: A bibliometric study - Albanaes, Patrícia (2015)
The university’s processes of tutoring and mentoring have been described as relevant toolsfor overall development and academic integration of the university student and overalldevelopment of the university student, and academic integration. This study conducted a bibliometric review about tutoring and mentoring programs in Brazilian universities between 1998 and 2013 in order to map existing initiatives, configuration, objectives, key findings and relevance. After consulting CAPES Repositorium, SciELO, INDEXPsi e BVS-Psi, 31 papers were analyzed. Most studies in the area of health were conducted in public institutions with qualitative methods, in the southeast and northeast of Brazil. Results indicated positive evaluation of the experiences, and point to aspects to be considered in future projects.